New Interventional Therapies beyond Stenting to Treat ST-Segment Elevation Acute Myocardial Infarction - Pablo Vidal-Calés; Pedro L. Cepas-Guillén; Salvatore Brugaletta; Manel Sabaté (Journal of Cardiovascular Development and Disease, 2021)
Myocardial infarction remains the principal cause of death in Europe. In patients with ST-segment-elevation myocardial infarction (STEMI), a promptly revascularization with primary percutaneous intervention (PCI) has transformed prognosis in the last decades. However, despite increasing successful PCI procedures, mortality has remained unchanged in recent years. Also, due to an unsatisfactory reperfusion, some patients have significant myocardial damage and suffer left ventricular adverse remodeling with reduced function—all that resulting in the onset of heart failure with all its inherent clinical and socioeconomic burden. As a consequence of longer ischemic times, distal thrombotic embolization, ischemia-reperfusion injury and microvascular dysfunction, the resultant myocardial infarct size is the major prognostic determinant in STEMI patients. The improved understanding of all the pathophysiology underlying these events has derived to the development of several novel therapies aiming to reduce infarct size and to improve clinical outcomes in these patients. In this article, based on the mechanisms involved in myocardial infarction prognosis, we review the new interventional strategies beyond stenting that may solve the suboptimal results that STEMI patients still experience.